PENGARUH RETURN ON ASSETS, RETURN ON EQUITY, DAN DEBT RATIO TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Hanifah Hanifah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2020)
This research was conducted with the aim to know the effect of return on assets, return on equity, and debt ratio on financial distress in Textile and Garment companies listed on the Indonesia Stock Exchange (BEI) for the 2013-2017 period both partially and simultaneously.The research method used in this study is a quantitative research method and descriptive research, the population of this study are all Textile and Garment companies listed on the Indonesia Stock Exchange (BEI) 2013-2017 period, as many as 18 companies. The research sample of 11 companies with 2013-2017 financial statement data with 55 research data. The sampling technique uses purposive sampling. Data analysis techniques using descriptive statistics and logistic regression analysis with processing techniques using SPSS 20.It was concluded that the results of the coefficient of determination using Nagelkerke's R Square of 80.4% and the results of the hypothesis test of this study that is either partially or simultaneously return on assets, return on equity, and debt ratio influence and significantly to financial distress. Suggestions for company, by increasing company performance so that companies avoid financial distress. For other researchers, it is recommended to add other independent variables besides return on assets, return on equity and debt ratio to things that might affect financial distress.